Fisheries issues in WTO and ACP-EU trade negotiations - Grynberg, Roman (Commonwealth Secretariat LondonGB, 2003)
Addresses the future of relations between the ACP and EU in the area of fisheries. Looks at the increasingly complex and interdependent ACP and EU fisheries relationship. Considers not only the past experience of the Common Fisheries Policy (CFP) but also describes the context of the CFP and why the EC has experienced such difficulties with this particular model. Considers the new evolving CFP and how it is viewed by various EU member states and focuses on the Conservation and Structural Policy of the EU within the context of the CFP. Arrives at far reaching conclusions and recommendations regarding the future of the relationship between the EU and the coastal ACP states.